Circadian Genes as Therapeutic Targets in Pancreatic Cancer - García-Costela, María; Escudero-Feliú, Julia; Puentes-Pardo, Jose D.; San Juán, Sara Moreno; Morales-Santana, Sonia; Ríos-Arrabal, Sandra; Carazo, Ángel; León, Josefa (Frontiers in Endocrinology, 2020)
Pancreatic cancer is one of the most lethal cancers worldwide due to its symptoms, early metastasis, and chemoresistance. Thus, the mechanisms contributing to pancreatic cancer progression require further exploration. Circadian rhythms are the dairy oscillations of multiple biological processes regulated by an endogenous clock. Several evidences suggest that the circadian clock may play an important role in the cell cycle, cell proliferation and apoptosis. In addition, timing of chemotherapy or radiation treatment can influence the efficacy and toxicity treatment. Here, we revisit the studies on circadian clock as an emerging target for therapy in pancreatic cancer. We highlight those potential circadian genes regulators that are commonly affected in pancreatic cancer according to most recent reports.